ANALISIS KINERJA DAN NILAI TAMBAH AGROINDUSTRI TAHU DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Muhamad Hary Panuju,; Teguh Endaryanto; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the raw material procurement system based on the elements of raw materials, the performance of production, and added value of the products.  The research method used in this research was a case study method on ‘Tahu Ibu Lis’ tofu agroindustry in Gadingrejo Urban Village, Gadingrejo Sub-district, Pringsewu Regency.  The location of research was determined purposively with the consideration that Tahu Ibu Lis agroindustry was one of agroindustries on the center of tofu production and the biggest production of tofu in Gadingrejo.  Tahu Ibu Lis agroindustry had many products, they were tahu pong, tahu kepal, tahu putih, tahu kuning, oncom, and keripik tahu.  Research was conducted in Mei – June 2019 and data analysis method used was qualitative and quantitative descriptive analysis and analysis of added value.  The study shows that the agroindustry has fulfilled the six components of raw materials procurement, i.e. time, place, price, type, quality, and quantity.  The production performance of the agroindustry had not been good because it had not fulfilled the capacity and flexibility components but the rests are good.  Tahu Ibu Lis agroindustry was viable because it had positive added value.Key words: added value, performance of production, tofu